Educação em direitos humanos e suas expressões no cotidiano escolar: um olhar avaliativo sobre a realidade educacional de Quixadá - Costa, Francisca Fábricia Teodoro (2020)
The present dissertation embodies the reflections and analytical findings of a research that proposed to evaluate the implementation of Education in Human Rights (EDH), from the local context of the education policy of the municipality of Quixadá (CE). As a reference in this evaluative research, we assume two plans: the National Plan for Education in Human Rights - (PNEDH) and the Municipal Plan for Education in Quixadá - (PME), since the municipality does not have a municipal plan focused on EDH. The research axis is circumscribed based on the following questions: How to analyze the implementation of Education in Human Rights, with only a few Brazilian cities exceptionally having a municipal human rights plan? And yet, to what extent has the Human Rights Education perspective been implemented in Quixadá's municipal educational public policy? Throughout the paths and developments of this evaluative investigation, central categories of analysis were worked on: human rights, Brazilian education, human rights education, public policies and public policy evaluation. In this direction, we had as a theoretical basis and key reference the contributions developed by Noberto Bobbio, Hannah Arendt, Paulo Freire, Murilo de Carvalho, Marilena Chauí, Nancy Fraser, Erasto Mendonça and Boaventura de Sousa Santos, which in their analyzes constituted true open paths and evaluative windows. We adopted, as a field of investigation, the EEF José Jucá school, of the municipal education network, having as protagonists subjects of the research, the managers, coordinators, teachers and students who built and experience today the elements proposed in educational documents, such as the Municipal Plan of Education (PME) and the Pedagogical Political Project (PPP) of the educational institution. In the methodological approach, we favor the perspective of in-depth assessment, engendering a qualitative research and assuming an anti-hegemonic stance in the epistemic field of public policy evaluation. To give concreteness to the analytical reflections, we developed multiple investigative dimensions, highlighting: bibliographic research, documentary research and field research. Specifically, the field research was developed through systematic observations and open interviews in terms of a statement, as well as informal dialogues with the different subjects. For the analysis of the material surveyed, we used content analysis, inspired by Bardin, from the founding categories of the research, embodied in major themes. Among the research findings, we configure limitations and possibilities regarding the implantation of EDH in the scenario of basic education in Quixadá and specifically in the school context of EEF José Jucá. Therefore, we list the main limitations: the invisibility of institutional documents such as the PME and the PPP by the subjects who are protagonists of the research; school management sometimes crossed by centralizing actions; extreme precariousness of the institution's physical structure; overcrowding in classrooms; teacher devaluation; experiences of bullying, racism, prejudice; increasing cases on the part of students with anxiety, depression and mutilation; Child labor; weakened family relationships; inexistence of participative spaces such as the student union. Such limitations thus constitute real violators of human rights in the school environment. Despite all the dilemmas and challenges, we identified potentialities: the progress of projects that dialogue with the perspective of EDH; the partnership with public policies and local universities; configurations of the institution's teaching staff; team work developed by professionals and educators; the protagonism of the students. In addition, we identified evidence of an education beyond the walls of the school, with the support of teaching innovation in the methodological field, already idealized by some teachers of the institution. We also reaffirm as a potentiality the possibility for the municipality to format a proposal focusing on human rights education, in the format of the PMEDH, or even the construction of an Action Plan on human rights by the school, subsidized by the reflections undertaken in the present study. Thus, we intend to experience the social function of research embodied in this dissertation, returning its findings to the subjects and to the field.